A Combinatorial Auction Protocol among Versatile Experts and Amateurs - Ito, Takayuki; Yokoo, Makoto; Matsubara, Shigeo (Autonomous Agents and Multiagent Systems: Proceedings, 3rd International Joint Conference, New York City, New York, 2004., 2004)
Auctions have become an integral part of electronic commerce and a promising field for applying multi-agent technologies. Correctly judging the quality of auctioned items is often difficult for amateurs, in particular, in Internet auctions. However, experts can correctly judge the quality of items. In this situation, it is difficult to force experts to tell the truth and attain an efficient allocation since they have a clear advantage over amateurs; without some reward they cannot be expected to reveal their valuable information. In our previous work, we successfully develop such auction protocols under the following two cases: (1) a single-unit auction among experts and amateurs, and (2) a combinatorial auction among single-skilled experts and amateurs. In this paper we focus on versatile experts, who have interest in and expert knowledge of the qualities of several items. In the case of versatile experts, there are several problems, e.g., free riding problems, if we simply extend the previous VCG-style auction protocol. Thus, in this paper, we employ a PORF (price-oriented, rationing-free) protocol for designing our new protocol to realize a strategy-proof auction protocol for experts. In the protocol, the dominant strategy for experts is telling the truth. Also for amateurs, telling the truth is the best response when two or more experts select the dominant strategy. Furthermore, the protocol is false-name-proof.